Zastosowanie Nordic Walking w turnusie rehabilitacyjnym osób po usunięciu krtani = Use of Nordic Walking in a rehabilitation of the people after total laryngectomy - Agnieszka Hamerlińska - Latecka (Kazimierz Wielki University, 2016)
Hamerlińska - Latecka Agnieszka. Zastosowanie Nordic Walking w turnusie rehabilitacyjnym osób po usunięciu krtani = Use of Nordic Walking in a rehabilitation of the people after total laryngectomy. Journal of Education, Health and Sport. 2016;6(10):646-652. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.221350 http://ojs.ukw.edu.pl/index.php/johs/article/view/4111     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.10.2016. Revised 02.10.2016. Accepted: 21.10.2016.       Zastosowanie Nordic Walking w turnusie rehabilitacyjnym osób po usunięciu krtani   Use of Nordic Walking in a rehabilitation of the people after total laryngectomy     Agnieszka Hamerlińska - Latecka   Wydział Pedagogiki i Psychologii, Uniwersytet Kazimierza Wielkiego w Bydgoszczy   Słowa kluczowe: laryngektomia, logopeda, Nordic Walking, rehabilitacja, turnus Key words: laryngectomy, speech therapist, Nordic Walking, rehabilitation, holidays health   Streszczenie Turnusy rehabilitacyjne dla osób po usunięciu krtani organizowane są średnio raz do roku. Specjalistami prowadzącymi zajęcia podczas takich wyjazdów są najczęściej: fizjoterapeuta, psycholog i logopeda. Celem takich turnusów jest usprawnianie fizyczne, psychiczne i społeczne. Celem niniejszego artykułu jest przedstawienie wyników badań dotyczących zastosowania przez osoby po laryngektomii całkowitej metody Nordic Walking podczas pobytu na wczasach zdrowotnych.   Abstract Rehabilitation for patients after laryngectomy are organized on average once a year. Specialists lecturers during such trips are the most common: physical therapist, psychologist and speech therapist. The purpose of these camps is the improvement of the physical, mental and social. The purpose of this article is to present the results of studies regarding the application by a person after total laryngectomy methods Nordic Walking while on holidays health.